Tumor invasion in the central airway is a risk factor for early‐onset checkpoint inhibitor pneumonitis in patients with non‐small cell lung cancer. Issue 12 (20th October 2020) - Moda, Mitsuhiro; Saito, Haruhiro; Kato, Terufumi; Usui, Ryo; Kondo, Tetsuro; Nakahara, Yoshiro; Murakami, Shuji; Yamamoto, Kouji; Yamada, Kouzo
Abstract : Background: Anti‐programmed death‐1 (PD‐1) immunotherapy can cause immune‐related pneumonitis, also known as checkpoint inhibitor pneumonitis (CIP). CIP that develops early after the initiation of anti‐PD‐1 immunotherapy is important because it is more severe than CIP that develops later. However, only a few studies have examined the risk factors for early‐onset CIP. Previous studies have reported several risk factors for CIP, including imaging findings of airway obstruction adjacent to lung tumors. However, the utility of this factor is debatable. Therefore, we investigated potential risk factors for early‐onset CIP, including tumor invasion in the central airway (TICA), in patients with non‐small cell lung cancer (NSCLC) receiving anti‐PD‐1 therapy. Methods: We retrospectively analyzed the medical records and chest computed tomography scans of patients with NSCLC treated with anti‐PD‐1 antibodies at the Kanagawa Cancer Center in Japan between 1 January 2016, and 30 June 2018. The clinical characteristics and imaging findings, including TICA, were compared between patients with and without early‐onset CIP. Results: Data from 181 eligible patients (114 receiving nivolumab and 67 receiving pembrolizumab) were analyzed. Early‐onset CIP occurred in 13 of 79 patients (16.5%) with TICA and 2 of 102 patients (2.0%) without TICA. In multivariate analysis, the odds ratio of early‐onset CIP for patients with TICA was 8.2 (95% confidence interval [CI]: 1.98–34.0, P = 0.0037). Conclusions: TICA was strongly associated with early‐onset CIP in patients with NSCLC. Clinicians should carefully observe patients with TICA, especially within three months of anti‐PD‐1 antibody administration because of high CIP risk. Key points: Significant study findings: Tumor invasion in the central airway (TICA) was a predictor of early‐onset checkpoint inhibitor pneumonitis (CIP) TICA had good interobserver variability, indicating its utility in clinical practice Patients with TICA might have a higher immune status than patients without What this study adds: This is the first study focusing on risk factors for CIP limited to early‐onset CIP. Abstract : TICA was strongly associated with early‐onset CIP in patients with NSCLC. Clinicians should carefully observe patients with TICA, especially within three months of anti‐PD‐1 antibody administration because of high CIP risk.